Multi-dimensional Workload in Two Types of Nuclear Power Plant Simulators. (November 2019) - Reinerman-Jones, Lauren; Lin, Jinchao; Barber, Daniel; Matthews, Gerald; Hughes, Niav
Analog, full-scope, full-scale simulators with the fidelity to simulate all of the physical and underlying thermodynamics in the real system are representative of training simulators used by current operating nuclear power plants. However, digital simulators are becoming desirable to researchers and utility companies alike due to their increased accessibility and the capability of integrating new system upgrades. The present study compared operators' workload response in a given operating procedure using an analog, full-scope/scale simulator and a digital, part-task simulator. Subjective measures (NASA-TLX, MRQ, ISA) and physiological measures (electrocardiography) were used to profile workload response. The results suggested the feasibility of using digital simulators for research purposes with potential future implications for training.